Spatial variability of soil micronutrients under paddy (Oryza sativa)-wheat (Triticum aestivum) cropping system in irrigated plains - BUTTAR, TEJBIR SINGH; SHARMA, VIKAS (The Indian Journal of Agricultural Sciences, 2023)
Soil properties vary spatially over short distances and sometimes prove detrimental to crop productivity in farmlands even after uniform application of balanced nutrients. In the present study, spatial variability of micronutrients was studied in Chakroi farm of Sher-e-Kashmir University of Agricultural Sciences and Technology of Jammu (SKUASTJammu) during 2016 and 2017. Results indicated that mean concentrations of micronutrients were in the order of Fe > Mn > Cu > Zn both in surface and sub-surface layers. Exponential model was the best fit for all micronutrients in surface soil layer. Linear model was best fit for Cu and Gaussian model for Mn in the sub-surface layer. Whereas for Zn and Fe, the best fit was defined by exponential model. All the four micronutrients showed strong spatial dependence in surface layer, whereas in sub-surface layer Mn and Zn showed strong spatial dependence as compared to Cu. More than 60% of the area in the surface layer had Cu in the range of 2.0–2.8 mg/kg of soil. A very small area was under high range on the eastern side of the farm while in the sub-surface layer, Cu was unevenly distributed. The soil maps of Zn showed that it is above the critical value in surface layer while in sub-surface layer nearly 40% of the area had Zn in the deficient range. Fe was unevenly distributed and in the sub-surface layer it was higher in the southern and north-western parts of the farm. Mn was above the critical limit in both surface and sub-surface soils of the farm.